A QUALITATIVE STUDY OF VALUE CHAIN ANALYSIS MODEL IN UD. FILADELFIA - Ngangi, Gabriela Ribka; Tumewu, Ferdinand . (Universitas Sam Ratulangi, 2018)
Abstract: Value chain analysis can be used by companies to understand the sources, create or develop a competitive advantage. When a company can accentuate the existing values, they can make it as a competitive advantage to compete with the other company. The aim of this study is to analyze the value chain of UD. Filadelfia Bitung. This company need to maintain their performance so they can compete with other company. This research is using qualitative research method that explores the theories from several journals, articles, books and previous research. The type of this research is descriptive research. Population in this research is all elements that have an influence in analyzing the value chain analysis model in UD. Filadelfia Bitung. The results showed that in support activities UD. Filadelfia has an experienced lack in Firm Infrastructure, Human Resources, and Technology Development. In primary activities UD. Filadelfia has some problems in Operation, and Outbound Logistics. While the advantage of this company is in the procurement section. Related with the findings there will be several recommendations.Keywords: value chain analysis, competitive advantage, support activities, primary activities